PREVALENCE OF FASCIOLIASIS AND HEMATO-BIOCHEMICAL ALTERATIONS DUE TO BOVINE FASCIOLIASIS IN FUNTUA CENTRAL ABATTOIR KATSINA STATE, NORTH WESTERN NIGERIA - Shinkafi, Buhari Yusuf; Abdulhamid, Ahmed; Mohammed, Suleman; Kankia, Ibrahim Hamza; Yabo, Bala Aminu; Tukur, Adamu (FUDMA Journal of Sciences, 2026)
Fascioliasis remains an important parasitic disease of cattle with significant implications for animal health and productivity. This study investigated the prevalence, intensity, risk factors, and associated haematological and biochemical alterations of Fasciola spp. infection in cattle slaughtered at Funtua abattoir, Katsina State, Nigeria. Coprological examination of 134 cattle revealed a low prevalence of 3.73% (5/134), while 96.3% were uninfected. Despite the low prevalence, infected animals exhibited a mean egg count of 4.0 eggs per gram (EPG), corresponding to an egg intensity of 1,000, indicating a moderate parasite burden capable of sustaining environmental contamination and transmission. Sex-specific analysis showed a higher prevalence in males (4.34%) than females (3.41%). Age-specific distribution revealed the highest prevalence among cattle older than 5 years (5%), while no infection was recorded in younger age groups. Breed-wise distribution indicated the highest prevalence in Wadara (10%) and White Fulani (4.88%), with no infection detected in Red Bororo and Azawak breeds. Haematological assessment of infected cattle demonstrated significant reductions in erythrocytic parameters, including red blood cell count, haemoglobin concentration, and packed cell volume, confirming fascioliasis-associated anaemia. Infected animals also exhibited leukocytosis with marked lymphopenia, consistent with chronic parasitic infection and immune modulation. Biochemical analysis revealed elevated liver enzymes (ALT, AST, and ALP), increased bilirubin concentrations, and altered protein profiles, indicating hepatic damage and impaired liver function. These findings demonstrate that even low-prevalence fascioliasis can exert substantial haematological and biochemical disturbances, underscoring the need for sustained surveillance and effective control strategies.